(untitled) (IJM: Journal of Multidisiplinary, 2024)
Evaluation is a crucial stage that must be conducted after the implementation of educational activities. This evaluation process aims to reflect on every aspect of the program that has been carried out to determine the extent to which the program aligns with the initial planning and meets the set expectations. In the Merdeka curriculum, there are developments and innovations in learning evaluation, particularly through the development of formative and summative assessments. This research employs a qualitative research method with a descriptive approach. Information is collected through direct interviews, where the researcher actively engages in question-and-answer sessions to obtain comprehensive data. The findings of this research indicate that MAN 1 Surakarta has modified the curriculum with a focus on learning evaluation, especially through formative and summative assessments. Formative assessment is actively used in learning activities through observation, individual discussions, group presentations, and independent tasks. Summative assessment is conducted at the end of the learning phase using written tests, portfolios, performances, and projects. The implementation of formative and summative evaluation faces several obstacles, including teachers' difficulties in adapting to changes in the curriculum and educational standards.